Technological Properties of SiC-Based Ceramic Slurries for Manufacturing Investment Casting Shell Moulds - Małek, M.; Wiśniewski, P.; Matysiak, H.; Zagórska, M.; Kurzydłowski, K. J. (Archives of Metallurgy and Materials, 2014)
Abstract In this work technological properties of ceramic slurries based on silicon carbide were characterized. Silicon carbide and poly(vinyl alcohol) in an amount 6%, 10% and 15 wt. % as a solution were added to prepare the ceramic slurries. Solid phase content in ceramic slurries was 62, 5 wt.%. Plate weight test, pH, density, viscosity (measured by the Zhan 4# cup) and dynamic viscosity were investigated. Dipping test on wax model was done to measure adhesive properties. Characterization of SiC fillers powder was made by determination of grain size, density, chemical composition, Zeta potential and by use of scanning electron microscopy. Obtained results of ceramic slurries based on SiC meet standard specification in industrial investment casting and its properties are very promising for future application in investment casting of superalloys.